Mattoana Arajang di Kecamatan Ajangale Kabupaten Bone (Suatu Tinjauan Kebudayaan Islam) - Mastanning, Mastanning (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
Mattoana Arajang is a rite to offering sesajen which as a symbol of respect to memorize the respected ancestors of Ajangale-Bone Society. This ritual is still ongoing after the arrival of Islam. This ritual shows that the presence of Mattoana Arajang in Ajangale District which began to the local belief to Dewata SeuwaE. That local belief was trusted as a provider of the heritage to ensure the settlement of Buginese people in Bone. Based on people’s views about Mattoana Arajang that this ritual could be disappear by itself due to a deep understanding of Islamic teachings on the society. So, the Arajang should be stored in museum to ensure the maintenance of it. Furthermore, there is the main thing to be considered which is to do counseling due to this custom can violate the Islamic law.